2013
DOI: 10.1042/bj20130461
|View full text |Cite
|
Sign up to set email alerts
|

A novel DYRK1B inhibitor AZ191 demonstrates that DYRK1B acts independently of GSK3β to phosphorylate cyclin D1 at Thr286, not Thr288

Abstract: DYRK1B (dual-specificity tyrosine phosphorylation-regulated kinase 1B) is amplified in certain cancers and may be an oncogene; however, our knowledge of DYRK1B has been limited by the lack of selective inhibitors. In the present study we describe AZ191, a potent small molecule inhibitor that selectively inhibits DYRK1B in vitro and in cells. CCND1 (cyclin D1), a key regulator of the mammalian G1-S-phase transition, is phosphorylated on Thr(286) by GSK3β (glycogen synthase kinase 3β) to promote its degradation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
76
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(85 citation statements)
references
References 44 publications
8
76
0
1
Order By: Relevance
“…Two recent reports have now made clear that either DYRK1A or DYRK1B can promote Cyclin D1 degradation via direct phosphorylation of Thr286 but do not target Thr288 16 , 41 . Consistent with our results for the effect of DYRK1A in SH-SY5Y cells, Ashford et al 16 have found in the pancreatic carcinoma cell line PANC-1 that the DYRK1B-driven phosphorylation at Thr286 and turnover of Cyclin D1 were not reduced by GSK3β inhibition. Thus, DYRK1A and DYRK1B regulate Cyclin D1 stability independent of GSK3β activity at least in some cell types.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Two recent reports have now made clear that either DYRK1A or DYRK1B can promote Cyclin D1 degradation via direct phosphorylation of Thr286 but do not target Thr288 16 , 41 . Consistent with our results for the effect of DYRK1A in SH-SY5Y cells, Ashford et al 16 have found in the pancreatic carcinoma cell line PANC-1 that the DYRK1B-driven phosphorylation at Thr286 and turnover of Cyclin D1 were not reduced by GSK3β inhibition. Thus, DYRK1A and DYRK1B regulate Cyclin D1 stability independent of GSK3β activity at least in some cell types.…”
Section: Discussionsupporting
confidence: 92%
“…Although GSK3β was initially reported to phosphorylate Cyclin D1 on Thr286, 68 DYRK1B was later proposed to promote Cyclin D1 degradation by phosphorylation at Thr288 69 . Two recent reports have now made clear that either DYRK1A or DYRK1B can promote Cyclin D1 degradation via direct phosphorylation of Thr286 but do not target Thr288 16 , 41 . Consistent with our results for the effect of DYRK1A in SH-SY5Y cells, Ashford et al 16 have found in the pancreatic carcinoma cell line PANC-1 that the DYRK1B-driven phosphorylation at Thr286 and turnover of Cyclin D1 were not reduced by GSK3β inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2D), suggesting that GSK3β may not be implicated in BafA1-induced Cyclin D1 turnover in HCC cells. Previous studies, in addition to more recent work in our laboratory have shown that DYRK1B (dual-specificity tyrosine phosphorylation-regulated kinase 1B) promotes the turnover of Cyclin D1 in a GSK3β-independent manner1112. A steady-state increase in DYRK1B protein levels was observed in both BEL7402 and HepG2 cells following treatment with BafA1 (Fig.…”
Section: Resultsmentioning
confidence: 62%
“…Cyclin D1 is a promoter of the G 1 -S transition in cell cycle and contains a phosphodegron recognized by SCF E3 ligase with the FBXO4 or the CRL7 E3 ligase with the FBXW8 receptor subunits (223)(224)(225). Cyclin D1 functions in the G 1 phase when bound to CDK4.…”
Section: Disruption Of Synergistic Degrons and The Corresponding E3 Lmentioning
confidence: 99%